PENGARUH INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PERUSAHAAN LISTRIK NEGARA (PERSERO) PEMBANGKITAN SUMATERA BAGIAN UTARA SEKTOR PEMBANGKITAN PANDAN - Yulian, Nina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study, to determine the effect of incentives on employee productivity at PT. Perusahaan Listrik Negara (Persero) Generation of North Sumatra in the Pandan Generation Sector by drawing the hypothesis that there is an effect of incentives on employee work productivity at PT. State Electricity Company (Persero) Generation of Northern Sumatra Pandan Generation Sector. The research method used is descriptive correlational method, while to find out how much influence the independent variable has on the dependent variable with the simple linear regression analysis method and the calculation of the coefficient of determination. The author uses 44 respondents as a sample drawn from the entire population. The results showed a positive relationship between incentives and employee work productivity at PT. Perusahaan Listrik Negara (Persero) of the North Sumatra Generation in the Pandan Generation Sector of 0.62, so that if interpreted on a scale the values ​​can be categorized as strong. The regression equation obtained Y = 21.103 + 0.665 X which shows the effect of incentives on work productivity, which means that employee productivity will increase by the regression coefficient / slop (0.665) if the incentive variable is added by one unit. T test shows that the hypothesis is accepted to be correct, where t arithmetic 5.139> 2.018. While the coefficient of determination is known that incentives only affect 38.60% of work productivity and the remaining 61.40% is influenced by other factors not examined.